PENGARUH CURRENT RATIO (CR), DEBT TO ASSET RATIO (DAR), PERPUTARAN PERSEDIAAN (INVENTORY TURNOVER), DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN PROPERTY DAN REAL ESTATE DI BEI PERIODE 2012 – 2016 - Silvia, .; Jovani, Vinna; Fransisca, .; Grace, Catherine; Gunawan, Roby; Samosir, Hottua; Tampubolon, Jonris (Universitas Sam Ratulangi, 2018)
The research objective wasÂ to test and analyze the Effect of Current Ratio, Debt to Asset Ratio, Inventory Turnover, Company Size on Profitability in Property and Real Estate Companies listed on the Indonesia Stock Exchange (IDX) for the period 2012-2016 partially or simultaneously. The research used quantitative method. The population used in this study was the Property and Real Estate Companies listed on the Indonesia Stock Exchange with a total of 46 companies in the period 2012-2016. The sample in this study used data takingÂ by means of purposive sampling. The number of samples used in this study were 31 companies with 155 observations. The results obtained were Current Ratio partially did not have a significant effect on Profitability. Partially Debt to Assets Ratio had no significant effect on profitability. Inventory Turnover in parallel l did not have significant effect on profitability. The size of the company partially had a positive and not significant effect on profitability. Current Ratio, Debt to Assets Ratio, Inventory Turnover and Company Size simultaneously did not have significant effect on Profitability in Property and Real Estate Companies listed on the Indonesia Stock Exchange for the period 2012-2016.Keywords: Current ratio (CR), Debt to assets ratio (DAR), Inventory Turnover, Company Size, Profitability